HAMSTRING INJURIES IN MAJOR AND MINOR LEAGUE BASEBALL: ARE THEY PREVENTABLE?. Issue 4 (1st February 2017) - Silvers-Granelli, Holly; Zachazewski, James; Li, Bernard; Insler, Stephanie; Mandelbaum, Bert; Ahmad, Christopher; Snyder-Mackler, Lynn
Abstract : Background: Hamstring injuries are the leading cause of time loss injury in professional baseball, accounting for 6% of all injuries. Objective: To test the efficacy of a hamstring injury prevention program (HIP) designed to address the incidence of acute and chronic hamstring injuries and re-injuries that occur in professional baseball. Design: Prospective cluster cohort study. Setting: Major (MAJ) and Minor (MIN) League Professional Baseball (USA). Patients (Participants): One Major and Minor League organization served as the intervention (INT) team; which encompassed Rookie, Fall Ball, Class A, AA, AAA and MAJ rosters (6 total teams). A total of 213 athletes were consented: MIN: N=173 and MAJ: N=40 . Intervention: Athletes completed a questionnaire detailing their HSI history. The HIP was disseminated to the medical staff, which was instructed on program implementation. Main Outcome Measurements: The data was analysed for program compliance and hamstring injury (HSI) rates compared to the control group (CON). Results: There were 2 HSI's in the INT vs. 79 in the CON in the MAJ (IR: 0.025 INT vs 0.068 CON, p<0.05); constituting a 25% reduction in HSI. There were 7 HSI's in the INT vs. 297 in the CON (IR: 0.039 INT vs. 0.065 CON, p<0.05), constituting a 40% reduction in MIN HSI. There was a significant reduction in time loss due to injury. There were 9 INT vs. 25.9 CON days lost, resulting in a 65.3% reduction in time loss in the MAJ (p<0.05). The Minor League reported 11.63 INT vs. 21.3 CON days lost, resulting in a 45.3% reduction in time loss (p<0.05). Conclusions: The reduction in HSI is consistent with existing literature with respect to the efficacy of an HIP to reduce HSI in athletes. This study is continuing for an additional competitive season (three year prospective).